Fides, dialogus and virtus: Re-examining the theological hermeneutics of the Reformation period - Jun Wang (HTS Teologiese Studies/Theological Studies)
Modern hermeneutics often oversimplifies the rich intellectual tradition of theological hermeneutics from the Reformation period, neglecting its complexity and depth. This study aims to re-examine this tradition by focusing on three often overlooked themes: the relationship between understanding and faith [fides], the dialogical nature of understanding [dialogus], and the virtue [virtus] of the interpreter. Through an in-depth analysis of early theological hermeneutic thought, the study reveals that the process of understanding is profoundly influenced by faith, possesses a dialogical character, and is grounded in the moral qualities of the interpreter. These findings challenge the simplified assessments of the theological tradition by modern hermeneutics and provide new perspectives for contemporary discussions on theories of understanding.